Surface-enhanced Raman spectroscopy combined with stable isotope probing to monitor nitrogen assimilation at both bulk and single-cell level - Cui, L; Yang, K; Zhou, G; Huang, W; Zhu, Y (American Chemical Society, 2017)
Microbe-mediated biogeochemical cycle of nitrogen is a critical process in the environment. In this study, surface-enhanced Raman spectroscopy combined with 15N stable isotope probing (SERS-15N SIP) was developed as a new, non-destructive, and robust approach to probe nitrogen assimilation by bacteria at both bulk and single-cell level, and from pure culture to environmental microbial community. Multiple distinguishable SERS band shifts were observed and displayed a linear relationship with 15N content, due to the substitution of ‘light’ nitrogen by ‘heavier’ 15N stable isotope. These shifts, especially in 730 cm-1 band, were highly distinguishable and universal in different bacteria, providing a robust indicator for nitrogen assimilation in bacteria. SERS-15N SIP was also demonstrated in important N2-fixing bacteria via 15N2 incubations. The same prominent shifts as that induced by 15NH4Cl were observed, indicating the applicability of SERS-15N SIP to different nitrogen sources. SERS-15N SIP was further applied to environmental microbial community via 15NH4Cl, 15NO3, and 15N2 incubation. Bacteria- and nitrogen source-dependent activity in nitrogen assimilation were revealed in environmental microbial community, pointing to the bacterial diversity and necessity of single-cell level investigation. Finally, by mixing optimized ratio of bacteria with Ag NPs, explicit single-cell SERS-15N SIP was obtained. The non-destructive SERS-15N SIP approach will be useful not only to identify active nitrogen-assimilating cells, but also enable Raman activated cell sorting and down-stream genomic analysis, which will bring in deep insights into nitrogen metabolism of environmental microorganisms.